Weather-resistant and anti-yellowing chlorinated alkane intumescent fire-retardant coating stabilization process
Patent Information
- Application Number
- CN202611485390.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明的目的是提供一种耐候抗黄变氯化烷烃膨胀型防火涂料稳定工艺,解决氯化烷烃在膨胀型防火涂料体系中因热稳定性不足和光氧化降解而导致的黄变及耐候性劣化问题
本发明通过将乙二醇缩水甘油醚与环氧大豆油中的环氧基团作为氯化氢捕获剂、甲基锡硫醇盐热稳定剂作为不稳定碳氯键的置换稳定剂、亚磷酸三苯酯作为甲基锡硫醇盐热稳定剂的再生协效剂,并辅以2-羟基-4-正辛氧基二苯甲酮对紫外光引发降解的源头抑制和四[-(3,5-二叔丁基-4-羟基苯基)丙酸]季戊四醇酯对自由基链式反应的终止作用,在氯化烷烃基体中形成了涵盖光稳定、热稳定和氧化稳定三重防护功能的高效复合稳定剂体系。该高效复合稳定剂体系中各组分之间存在明确的协同作用关系:乙二醇缩水甘油醚和环氧大豆油捕获氯化氢降低体系酸性,为甲基锡硫醇盐热稳定剂维持活性配位结构提供低酸度环境;亚磷酸三苯酯将失活的锡氯化物还原再生,延长甲基锡硫醇盐热稳定剂的有效稳定周期;2-羟基-4-正辛氧基二苯甲酮从光引发环节降低碳氯键均裂概率,减少需要甲基锡硫醇盐热稳定剂和环氧化合物处理的降解产物总量;四[
-(3,5-二叔丁基-4-羟基苯基)丙酸]季戊四醇酯终止已经引发的自由基链反应,作为整个高效复合稳定剂体系的最后一道防线。上述各组分的协同作用使高效复合稳定剂体系能够在光照、热和氧气协同作用的服役环境下持续抑制氯化烷烃的脱氯降解,从而抑制涂膜黄变和色差增大。
Smart Images

Figure CN122978760A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical coatings technology, and more specifically, to a stabilization process for a weather-resistant and anti-yellowing chlorinated alkane intumescent fire-retardant coating. Background Technology
[0002] Intumescent fire-retardant coatings use ammonium polyphosphate, pentaerythritol, and melamine as the basic framework of their intumescent flame-retardant system. Chlorinated alkanes, due to their combined flame-retardant and plasticizing effects, are widely incorporated into this system to assist in flame retardancy and improve the foaming and charring properties of the coating film. Chlorinated alkanes, in outdoor service environments, must withstand long-term exposure to ultraviolet radiation, high temperatures, and the synergistic effects of oxygen, making them one of the key factors affecting the weather resistance of intumescent fire-retardant coatings.
[0003] In the prior art, to address the degradation and discoloration problem of chlorinated alkanes in coating systems, a single stabilizer is typically used to modify the chlorinated alkanes in order to inhibit their dechlorination degradation during service.
[0004] However, single stabilizers have drawbacks such as low thermal stabilization efficiency, insufficient UV protection coverage, and poor compatibility with coating systems, making it impossible to simultaneously cover multiple degradation pathways such as photoinitiation, thermal promotion, and free radical chain propagation. The unstable carbon-chlorine bonds contained in the molecular structure of chlorinated alkanes are prone to homolytic cleavage under the synergistic effect of the above multiple factors, initiating free radical chain oxidative degradation reactions and releasing hydrogen chloride gas. This leads to technical problems such as gradual darkening of color, obvious yellowing, and increased color difference in the coating film after long-term outdoor use. At the same time, the degradation products have a negative impact on the adhesion of the coating matrix resin and the integrity of the expanded carbonized layer. Summary of the Invention
[0005] The purpose of this invention is to provide a stabilization process for weather-resistant and anti-yellowing chlorinated alkane intumescent fire-retardant coatings, solving the problems of yellowing and weather resistance degradation caused by insufficient thermal stability and photo-oxidative degradation of chlorinated alkanes in intumescent fire-retardant coating systems.
[0006] At least one embodiment of this disclosure provides a stabilization process for a weather-resistant and anti-yellowing chlorinated alkane intumescent fire-retardant coating. The stabilization process includes: a step of preparing a high-efficiency composite stabilizer, a step of preparing a chlorinated alkane base material, a step of compounding the chlorinated alkane base material with the high-efficiency composite stabilizer to obtain stabilized chlorinated alkane, and a step of adding the stabilized chlorinated alkane to the intumescent fire-retardant coating formulation system to prepare the intumescent fire-retardant coating.
[0007] For example, in the stabilization process provided in at least one embodiment of this disclosure, the step of preparing the high-efficiency composite stabilizer includes: mixing ethylene glycol glycidyl ether, methyl tin thiolate heat stabilizer, triphenyl phosphite, epoxidized soybean oil, 2-hydroxy-4-n-octyloxybenzophenone, and pentaerythritol tetrapropionate at 60-80°C for 20-40 minutes; the mass parts of each component are: 2-5 parts of ethylene glycol glycidyl ether, 1-3 parts of methyl tin thiolate heat stabilizer, 1-3 parts of triphenyl phosphite, 3-8 parts of epoxidized soybean oil, 0.5-2 parts of 2-hydroxy-4-n-octyloxybenzophenone, and 0.5-1.5 parts of pentaerythritol tetrapropionate.
[0008] For example, in the stabilization process provided in at least one embodiment of this disclosure, the mass parts of each component when preparing the high-efficiency composite stabilizer are: 3 parts of ethylene glycol glycidyl ether, 2 parts of methyl tin thiolsate heat stabilizer, 2 parts of triphenyl phosphite, 5 parts of epoxidized soybean oil, 1 part of 2-hydroxy-4-n-octyloxybenzophenone, and 1 part of pentaerythritol tetrapropionate.
[0009] For example, in the stabilization process provided in at least one embodiment of this disclosure, the order of adding each component when preparing the high-efficiency composite stabilizer is as follows: first, epoxidized soybean oil and ethylene glycol glycidyl ether are premixed evenly at 60°C, then triphenyl phosphite, pentaerythritol tetrapropionate and 2-hydroxy-4-n-octyloxybenzophenone are added in sequence, and finally, methyltin thiolsate heat stabilizer is added after the above components are fully dissolved, and the mixing temperature is controlled at 60-70°C.
[0010] For example, in the stable process provided in at least one embodiment of this disclosure, the step of preparing chlorinated alkane base material includes: adding straight-chain alkane raw materials and dispersants into a chlorination reactor, introducing dry chlorine gas and carrying out a chlorination reaction according to a gradient temperature program, and obtaining a chlorinated alkane base material with a chlorine content of 68% to 72% after deacidification, water washing and drying; the gradient temperature program includes three stages: the first stage is to introduce chlorine gas at 60 to 70°C and react for 1 to 2 hours; the second stage is to raise the reaction temperature to 75 to 85°C and continue to introduce chlorine gas and react for 1.5 to 3 hours; the third stage is to raise the reaction temperature to 85 to 95°C and continue to introduce chlorine gas and react for 1.5 to 3 hours; the total reaction time is controlled at 4 to 8 hours.
[0011] For example, in the stable process provided in at least one embodiment of this disclosure, the heating rate between the first stage and the second stage and between the second stage and the third stage is controlled at 1 to 3 °C / min; the dispersant is sodium dodecyl sulfate, and the amount added is 0.1% to 0.5% of the mass of the straight-chain alkane raw material.
[0012] For example, in the stable process provided in at least one embodiment of this disclosure, after the third stage reaction is completed, dry nitrogen gas is introduced into the reaction system at 85-90°C for 15-30 minutes, followed by neutralization and deacidification with a sodium carbonate aqueous solution of 5%-10% by mass until the pH of the system is 7.0-8.0, washing with deionized water until the pH of the washing solution is 6.5-7.5, and drying with forced air at 80-100°C for 2-4 hours.
[0013] For example, in the stable process provided in at least one embodiment of this disclosure, the obtained chlorinated alkane base material is a straight-chain alkane chloride with a base carbon chain length of C14 to C17, a viscosity of 500 to 3000 mPa·s, and a thermal decomposition initiation temperature of not less than 180°C.
[0014] For example, in the stabilization process provided in at least one embodiment of this disclosure, when the chlorinated alkane base material and the high-efficiency composite stabilizer are compounded, the mass ratio of the two is 100:0.5 to 2, and they are stirred and mixed at 60 to 80°C for 30 to 60 minutes; further, the mass ratio of the chlorinated alkane base material and the high-efficiency composite stabilizer is 100:1.5, the stirring temperature is 75°C, the stirring time is 60 minutes, and the compounding operation is carried out under nitrogen protection with a purity of not less than 99.9%.
[0015] For example, in the stabilization process provided in at least one embodiment of this disclosure, in the step of preparing the intumescent fire-retardant coating, stabilized chlorinated alkanes are added to the intumescent fire-retardant coating formulation system at a mass percentage of 15% to 25%, and the intumescent fire-retardant coating is prepared at a processing temperature not exceeding 150°C; the mass parts of each component in the formulation system are: ammonium polyphosphate 18 to 25 parts, pentaerythritol 8 to 15 parts, melamine 8 to 15 parts, stabilized chlorinated alkanes 15 to 25 parts, rutile titanium dioxide 3 to 7 parts, water 15 to 22 parts, and the remainder being coating film-forming resin and additives.
[0016] At least one embodiment of this disclosure also provides an intumescent fire-retardant coating, which is prepared by the weather-resistant and anti-yellowing chlorinated alkane intumescent fire-retardant coating stabilization process described in any embodiment of this disclosure.
[0017] This invention utilizes ethylene glycol glycidyl ether and the epoxy groups in epoxidized soybean oil as hydrogen chloride scavengers, methyl tin thiolate as a heat stabilizer for unstable carbon-chlorine bonds, and triphenyl phosphite as a regeneration synergist for the methyl tin thiolate heat stabilizer, supplemented by 2-hydroxy-4-n-octyloxybenzophenone to inhibit UV-induced degradation at its source and tetra[ [3,5-Di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester terminates the free radical chain reaction, forming a highly efficient composite stabilizer system in the chlorinated alkane matrix that provides triple protection against light, heat, and oxidation. This solves the technical problem that single stabilizers cannot continuously inhibit the dechlorination degradation of chlorinated alkanes under long-term service conditions, leading to yellowing and increased color difference in fire-retardant coatings. It achieves the technical effect of continuously inhibiting the dechlorination degradation of chlorinated alkanes under the synergistic effects of light, heat, and oxygen in service environments, thereby suppressing yellowing and increased color difference in the coating film. Simultaneously, by adopting […] during the preparation stage of chlorinated alkanes… By using a gradient temperature chlorination process, the proportion of unstable chlorine atoms in the molecular structure is reduced, ensuring that the thermal decomposition initiation temperature of the resulting chlorinated alkane base material is not lower than 180℃. Compared with the product obtained by the one-step isothermal chlorination process, the product has a higher thermal decomposition initiation temperature, providing a wider temperature window for thermal safety during subsequent coating processing and service. In addition, by controlling the amount of stabilized chlorinated alkane added to 15% to 25% and limiting the processing temperature to below 150℃, a balance is achieved between flame retardant performance and color stability, avoiding local degradation and discoloration caused by uneven dispersion due to excessive addition. Attached Figure Description
[0018] Figure 1 This is a process flow diagram of the preparation process of the weather-resistant and anti-yellowing chlorinated alkane intumescent fire-retardant coating provided in the embodiments of the present invention;
[0019] Figure 2 This is a schematic diagram comparing the total color difference ΔE* of each group of samples after aging for 500 hours, provided in the embodiments of the present invention.
[0020] Figure 3 This is a schematic diagram comparing the starting temperatures of gradient heating chlorination and one-step isothermal chlorination thermal decomposition provided in an embodiment of the present invention.
[0021] Figure 4 This is a schematic diagram showing the changes in b-chromaticity coordinates (Δb) of each group of samples before and after aging, provided in the embodiments of the present invention.
[0022] Figure 5 This is a schematic diagram of the color difference components (ΔL, Δa, Δb*) of each component in Examples 1-5 provided by the present invention. Detailed Implementation
[0023] This invention discloses a stabilization process for weather-resistant and anti-yellowing chlorinated alkane intumescent fire-retardant coatings, solving the following technical problems in the prior art: Intumescent fire-retardant coatings typically use ammonium polyphosphate, pentaerythritol, and melamine as the intumescent flame-retardant system. Chlorinated alkanes are widely incorporated into this system due to their combined flame-retardant and plasticizing effects. However, the unstable carbon-chlorine bonds in the chlorinated alkanes' molecular structure are prone to homolytic cleavage under ultraviolet light, high temperature, and the synergistic effect of oxygen, initiating a free radical chain oxidation degradation reaction that releases hydrogen chloride gas. This leads to a gradual darkening and noticeable yellowing of the coating film. Simultaneously, the degradation products negatively impact the adhesion of the coating matrix resin and the integrity of the intumescent char layer. In existing technologies, the degradation and discoloration of chlorinated alkanes in coating systems is typically addressed by modifying the coating with a single stabilizer. However, single stabilizers suffer from drawbacks such as low thermal stability efficiency, insufficient ultraviolet protection coverage, and poor compatibility with the coating system. They cannot continuously inhibit the dechlorination degradation of chlorinated alkanes under long-term service conditions, resulting in yellowing and increased color difference in fire-retardant coatings after a period of outdoor use.
[0024] Step 1, Preparation of high-efficiency composite stabilizer Ethylene glycol glycidyl ether, methyl tin thiolate heat stabilizer, triphenyl phosphite, epoxidized soybean oil, 2-hydroxy-4-n-octyloxybenzophenone, and tetra[ The pentaerythritol ester of [-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] was weighed according to the mass fraction and placed in a stirred reactor. It was stirred and mixed at 60-80℃ for 20-40 minutes to allow the components to fully melt and dissolve, thus obtaining a uniform, transparent, and highly efficient composite stabilizer.
[0025] The mass proportions of each component are as follows: ethylene glycol glycidyl ether 2-5 parts, methyl tin thiolate heat stabilizer 1-3 parts, triphenyl phosphite 1-3 parts, epoxidized soybean oil 3-8 parts, 2-hydroxy-4-n-octyloxybenzophenone 0.5-2 parts, tetra[ 0.5 to 1.5 parts of pentaerythritol ester [3,5-di-tert-butyl-4-hydroxyphenyl)propionate].
[0026] It should be noted that the above-mentioned ethylene glycol glycidyl ether has an epoxy value of 0.60–0.75 eq / 100g, a viscosity of 8–15 mPa·s (25℃), and a number-average molecular weight of approximately 174 g / mol. It is a liquid epoxy compound. The epoxy groups contained in its molecular structure can undergo a ring-opening addition reaction with hydrogen chloride released during the degradation of chlorinated alkanes, capturing the active hydrogen chloride into stable chlorinated alcohol compounds, thus blocking the catalytic degradation chain of hydrogen chloride on the coating matrix from the source.
[0027] It should be noted that the methyltin thiolate heat stabilizer has a tin content of 16%–20% (calculated as Sn) and a sulfur content of 8%–12%. It is a colorless to pale yellow transparent liquid with a viscosity of 50–150 mPa·s (25°C). The methyltin thiolate heat stabilizer can undergo a coordination substitution reaction with the unstable allyl chloride structure formed in the early stages of chlorinated alkanes, replacing the unstable carbon-chlorine bond with a stable tin-chlorine bond. This prevents the growth of conjugated polyene sequences, thereby inhibiting yellowing caused by the extension of conjugated double bonds.
[0028] It should be noted that the molecular weight of the aforementioned triphenyl phosphite is 310 g / mol, the melting point is 22–25 °C, and the purity is ≥99%. As an auxiliary heat stabilizer, the trivalent phosphorus atoms of triphenyl phosphite can reduce and regenerate the tin chloride generated during the capture of hydrogen chloride by the methyltin thiolsate heat stabilizer into the active methyltin thiolsate form, thus extending the effective action period of the methyltin thiolsate heat stabilizer. At the same time, triphenyl phosphite itself can decompose hydrogen peroxide-like oxidation intermediates, interrupting the transmission pathway of free radical chain degradation reactions.
[0029] It should be noted that the above-mentioned epoxidized soybean oil has an epoxy value ≥ 6.0% (by mass fraction) and an iodine value ≤ 3.0 g. It is a light yellow oily liquid with an acid value ≤1.0 mg KOH / g and a viscosity of 300~500 mPa·s (25℃). The multiple epoxy groups in the epoxidized soybean oil molecule can act as a long-lasting hydrogen chloride scavenger, supplementing the hydrogen chloride absorption capacity of ethylene glycol glycidyl ether. Simultaneously, its long-chain fatty acid ester structure endows the highly efficient composite stabilizer with good compatibility with chlorinated alkanes, promoting the uniform dispersion of the highly efficient composite stabilizer in the chlorinated alkane matrix.
[0030] It should be noted that the molecular weight of the aforementioned 2-hydroxy-4-n-octyloxybenzophenone is 326 g / mol, its melting point is 45–50 °C, its maximum absorption wavelength is 325–330 nm, and its purity is ≥98%. 2-hydroxy-4-n-octyloxybenzophenone can selectively absorb ultraviolet radiation in the wavelength range of 280–380 nm, dissipating light energy as heat, reducing the photo-induced homolytic cleavage excitation of the carbon-chlorine bonds in chlorinated alkane molecules by ultraviolet light, and lowering the initiation rate of oxidative degradation from the photoinitiation stage.
[0031] It should be noted that the above four [ The molecular weight of pentaerythritol ester [-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] is 1177.6 g / mol, the melting point is 110–125℃, and the ash content is ≤0.1%. This indicates the methylene position adjacent to the carbonyl group in the carbon chain of propionic acid. Four [ The hindered phenolic hydroxyl group in the pentaerythritol ester of [3,5-di-tert-butyl-4-hydroxyphenyl)propionate can provide active hydrogen atoms to the peroxy radicals and alkoxy radicals generated during the oxidative degradation of chlorinated alkanes, terminating the free radical chain reaction and forming a dual protection of photostability and oxidative stability with 2-hydroxy-4-n-octyloxybenzophenone.
[0032] Furthermore, in step 1, the rotation speed of the stirring reactor should be controlled between 200 and 400 rpm, preferably 300 rpm, to ensure that the components are fully miscible in the molten state at 60 to 80°C, while avoiding the introduction of air bubbles due to excessively high rotation speed, which would affect the appearance uniformity of the high-efficiency composite stabilizer.
[0033] Furthermore, the preferred proportions of the above components by mass are as follows: 3 parts ethylene glycol glycidyl ether, 2 parts methyl tin thiolate heat stabilizer, 2 parts triphenyl phosphite, 5 parts epoxidized soybean oil, 1 part 2-hydroxy-4-n-octyloxybenzophenone, and tetra[ [3,5-Di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester 1 part. This preferred ratio achieves a synergistic balance between the hydrogen chloride capture equivalent of the epoxy group and the allyl chloride replacement capacity of the methyltin thiolate heat stabilizer. This effectively neutralizes the hydrogen chloride released during degradation and inhibits the growth of conjugated polyene structures, thereby maintaining the color stability of the coating system throughout its service life. The high-efficiency composite stabilizer obtained in step 1 should be a homogeneous, transparent liquid without obvious layering or precipitation. It can only be used in step 3 after passing visual inspection.
[0034] Furthermore, during the mixing of the components in step 1 at 60–80°C, the epoxy groups contained in ethylene glycol glycidyl ether exhibit a competitive side reaction within this temperature range, undergoing ring-opening addition with the thiol groups in the methyl tin thiol salt heat stabilizer. This leads to the consumption of active epoxy groups and a reduction in the effective thiol salt content of the methyl tin thiol salt heat stabilizer. To suppress the above side reaction, the order of addition of the components should be as follows: first, premix the epoxidized soybean oil and ethylene glycol glycidyl ether evenly at 60°C, then add triphenyl phosphite, tetramethyl phthalate, and tetramethyl phthalate in sequence. [3,5-Di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester and 2-hydroxy-4-n-octyloxybenzophenone were added. After the above components were fully dissolved, methyltin thiolsate heat stabilizer was added last. The mixing temperature was controlled within the lower limit of 60-70°C to reduce the ring-opening addition reaction rate between the epoxy group and the mercapto group, and to ensure that each active component maintains its complete chemical structure in the high-efficiency composite stabilizer.
[0035] Furthermore, during step 1, the methyltin thiolsate heat stabilizer is a compound containing organotin, which is irritating to the skin and respiratory tract. When weighing and dispensing, operators should wear chemical-resistant gloves and protective glasses, and the operation should be carried out in a fume hood or an environment with local exhaust ventilation. Triphenyl phosphite is irritating to the skin and eyes, and direct contact should be avoided when weighing. Small amounts of waste packaging materials and wiping materials containing organotin residues generated during the weighing and dispensing process must be collected separately as hazardous solid waste and disposed of by a professional waste treatment agency.
[0036] Step 2, Gradient chlorination preparation of chlorinated alkanes A straight-chain alkane feedstock and 0.1%–0.5% sodium dodecyl sulfate dispersant (by mass of the feedstock) are added to a chlorination reactor. After mixing thoroughly at room temperature, dry chlorine gas is introduced to carry out the chlorination reaction. The chlorination reaction is carried out according to the following gradient temperature increase program: First stage: Chlorine gas is introduced at 60-70℃ and reacted for 1-2 hours, allowing chlorine gas to slowly penetrate into the alkane molecular chain at low temperature, achieving preliminary uniform substitution; Second stage: Raise the reaction temperature to 75-85℃, continue to introduce chlorine gas and react for 1.5-3 hours. On the basis of the uniform chlorination established in the first stage, further promote the substitution reaction and promote the chlorine content to increase towards the target value. The third stage involves raising the reaction temperature to 85–95°C and continuing to introduce chlorine gas for 1.5–3 hours to complete deep chlorination, achieving a chlorine content of 68%–72%; the entire reaction time is controlled within 4–8 hours.
[0037] After the third stage reaction is completed, dry nitrogen gas is introduced into the reaction system at 85-90℃ for 15-30 minutes to fully remove residual free chlorine gas and generated hydrogen chloride gas. Subsequently, the mixture is neutralized and deacidified with sodium carbonate aqueous solution, washed with deionized water until the pH of the washing solution is 6.5-7.5, and dried with forced air at 80-100℃ for 2-4 hours to obtain a homogeneous chlorinated alkane base material. The chlorine content of the product is detected by gas chromatography, and it is confirmed that the chlorine content is within the range of 68%-72% to be qualified.
[0038] It should be noted that the preferred amount of sodium dodecyl sulfate dispersant added is 0.3% of the raw material mass. The sodium dodecyl sulfate dispersant improves the gas-liquid two-phase mass transfer interface in the reaction system, dispersing chlorine gas bubbles into finer bubbles in the liquid alkanes, increasing the gas-liquid contact area, thereby reducing over-chlorination and the formation of polychlorinated byproducts caused by excessively high local chlorine concentrations.
[0039] It should be noted that the key points of the above gradient temperature program are: the first stage, low-temperature slow chlorination, ensures that the hydrogen atoms at each carbon position on the alkane molecular chain are uniformly replaced, avoiding over-chlorination at certain carbon positions and the formation of structural defect sites; the second stage, medium-temperature accelerated chlorination, further promotes the substitution reaction based on the uniform chlorination established in the first stage; and the third stage, high-temperature deep chlorination, ensures that the total chlorine content meets the standard. Compared with one-step isothermal chlorination, the chlorinated alkane base material obtained by the gradient temperature program has a higher uniformity of chlorine atom distribution and a lower proportion of unstable chlorine atoms (such as chlorine at tertiary carbon positions and chlorine at allyl positions) in the molecular structure, thus giving the product a higher thermal decomposition initiation temperature.
[0040] Furthermore, the stirring speed during the chlorination reaction in step 2 should be controlled at 300-500 rpm, preferably 400 rpm, to ensure that the chlorine bubbles maintain a sufficiently uniform gas-liquid contact area in the liquid alkane. Combined with the interface improvement effect of sodium dodecyl sulfate dispersant, this effectively suppresses the overchlorination side reaction caused by excessively high local chlorine concentration.
[0041] Furthermore, in step 2, the heating rate between the first stage and the second stage and between the second stage and the third stage should be controlled at 1 to 3 °C / min, preferably 2 °C / min, so that the chlorination reaction rate at each carbon site can be smoothly transitioned, and the reaction rate can be prevented from increasing too quickly, which would result in overchlorination structural defects at the tertiary carbon site and allyl site in the molecular chain.
[0042] Furthermore, the purity of the dry chlorine gas introduced in step 2 shall not be less than 99.5% (volume fraction), and the chlorination reaction shall be carried out under normal pressure (0.1 MPa) throughout the process. Since the heat of reaction is significant when alkanes and chlorine undergo free radical substitution reaction, the chlorination reactor must be equipped with a jacketed cooling circulation system. The chlorine gas flow rate must be matched with the jacket cooling capacity of the chlorination reactor to ensure that the temperature inside the reactor is stably controlled within the set range at each gradient stage, and to prevent the system temperature from running out of control and uncontrollable free radical chain side reactions caused by excessive gas flow rate leading to the heat release rate exceeding the heat dissipation capacity.
[0043] Furthermore, the purity of the dry nitrogen used for nitrogen purging in the final stage of step 2 shall not be less than 99.9% (volume fraction), and the purging flow rate shall be controlled at 3 to 5 times the effective volume of the chlorination reactor per hour. Purging shall be carried out continuously for 15 to 30 minutes at 85 to 90°C to fully remove residual free chlorine and dissolved hydrogen chloride from the liquid phase and reduce the processing load of the subsequent sodium carbonate aqueous solution neutralization and deacidification step.
[0044] Furthermore, in step 2, the sodium carbonate aqueous solution used for neutralization and deacidification has a mass fraction of 5% to 10%. The neutralization operation should adjust the pH of the system to 7.0 to 8.0 before proceeding with the subsequent deionized water washing step. Compared with strong alkaline solutions, sodium carbonate aqueous solution has a lower tendency to catalytically hydrolyze the molecular chains of chlorinated alkane base materials, and can effectively remove residual hydrogen chloride while maintaining the integrity of the product's molecular structure.
[0045] Furthermore, in step 2, the amount of sodium carbonate aqueous solution used for neutralization and deacidification is calculated based on the neutralization equivalent. Taking the total molar amount of hydrogen chloride generated during the chlorination reaction as the benchmark, the amount of sodium carbonate added should be 1.05 to 1.10 times the theoretical neutralization equivalent to ensure that the residual hydrogen chloride is completely neutralized. After the neutralization operation is completed, deionized water washing should be performed at least 3 times, with the amount of water used for each wash not less than 0.5 times the volume of the material, until the pH of the washing solution stabilizes in the range of 6.5 to 7.5, so as to fully remove residual sodium carbonate and sodium chloride and other water-soluble inorganic salts, and prevent the residual inorganic salts from affecting the stability of the subsequent coating formulation system.
[0046] Furthermore, the thermal decomposition initiation temperature of the chlorinated alkane base material obtained in step 2 is characterized by thermogravimetric analysis. The determination is carried out under nitrogen atmosphere and heating rate of 10℃ / min. The temperature at which the sample mass loss reaches 5% of the initial mass is taken as the thermal decomposition initiation temperature. The thermal decomposition initiation temperature of qualified products should not be lower than 180℃.
[0047] Furthermore, during the chlorination reaction in step 2, chlorine is a highly irritating and corrosive toxic gas. The entire chlorination operation should be carried out in a dedicated workshop with a closed ventilation and negative pressure exhaust system. Operators should wear gas masks, acid and alkali resistant protective gloves, and goggles. The tail gas containing hydrogen chloride and free chlorine discharged from the tail gas outlet of the chlorination reactor and during the nitrogen purging stage must be neutralized and absorbed by an alkaline solution (sodium hydroxide aqueous solution, mass fraction 10% to 15%) absorption tower to ensure that the concentration of chlorine and hydrogen chloride in the exhaust gas meets the emission limits before it can be discharged into the atmosphere.
[0048] Furthermore, the wastewater containing sodium chloride, sodium carbonate, and trace amounts of chlorinated alkanes generated during the neutralization and deacidification process of sodium carbonate aqueous solution and deionized water washing in step 2 must be treated separately after oil-water separation: the separated oil phase containing chlorinated alkanes is collected separately as hazardous waste liquid and disposed of by a professional waste liquid treatment agency; the aqueous phase can be discharged into the wastewater treatment system only after neutralization and pH adjustment to 6-9.
[0049] Step 3: Combining high-efficiency composite stabilizer with chlorinated alkanes Weigh the chlorinated alkane base material obtained in step 2 and the high-efficiency composite stabilizer obtained in step 1 at a mass ratio of 100:(0.5~2) and add them to a stirring tank. Stir and mix at 60~80℃ for 30~60 minutes to allow the high-efficiency composite stabilizer to fully penetrate and uniformly disperse in the chlorinated alkane base, thereby obtaining stabilized chlorinated alkane.
[0050] It should be noted that the aforementioned chlorinated alkane base material is a liquid chlorinated paraffin with a chlorine content of 68%–72% (by mass fraction), a viscosity of 500–3000 mPa·s (25°C), and a basic carbon chain length of C14–C17, which is a straight-chain alkane chloride. The chlorine content range of 68%–72% was chosen because chlorinated paraffins within this range offer both sufficient flame retardancy and acceptable thermal stability in intumescent fire-retardant coatings. When the chlorine content is below 68%, the flame retardant effect is insufficient, and when it is above 72%, the carbon-chlorine bond density is too high, significantly increasing the tendency for thermal degradation.
[0051] Furthermore, the preferred mass ratio of the chlorinated alkane base material to the high-efficiency composite stabilizer is 100:1.5, the preferred stirring temperature is 75℃, and the preferred stirring time is 60 minutes. Under these conditions, the active components in the high-efficiency composite stabilizer can fully diffuse into the inter-chain spaces of the chlorinated alkane base material, forming a uniform stabilized distribution. The stabilized chlorinated alkane obtained in step 3 should be in a uniform liquid state. After sampling, the absorbance at 400 nm is measured by ultraviolet-visible spectrophotometry. Compared with the unstabilized chlorinated alkane, the absorbance increase should not exceed 0.05, thus determining that the dispersion uniformity of the high-efficiency composite stabilizer is qualified.
[0052] Furthermore, in step 3, the rotation speed of the stirring vessel should be controlled between 200 and 400 rpm, preferably 300 rpm. The shear force generated within this speed range is sufficient to allow the high-efficiency composite stabilizer to diffuse uniformly in the high-viscosity chlorinated alkane matrix, while avoiding local overheating caused by excessive shearing, which would affect the chemical integrity of the active components in the high-efficiency composite stabilizer.
[0053] Furthermore, during the compounding process in step 3, a trace amount of hydrogen chloride is released as an oxidative degradation side reaction under stirring conditions of 60–80°C. The released trace amounts of hydrogen chloride will preferentially consume the epoxy groups in the high-efficiency composite stabilizer, reducing the effective capture capacity of the high-efficiency composite stabilizer. In order to suppress the pre-consumption of the activity of the high-efficiency composite stabilizer by the above side reaction, the compounding operation in step 3 should be carried out under the protection of an inert gas (nitrogen, purity not less than 99.9%, volume fraction) to isolate the synergistic oxidative effect of oxygen on the chlorinated alkane base material at the compounding temperature, thereby minimizing the release of hydrogen chloride during the compounding process.
[0054] Step 4: Adding stabilized chlorinated alkanes to the fire-retardant coating formulation The stabilized chlorinated alkanes obtained in step 3 are added to the intumescent fire retardant coating formulation system at a mass percentage of 15% to 25%. The intumescent fire retardant coating is prepared by stirring, dispersing and grinding the components such as ammonium polyphosphate, pentaerythritol, melamine, rutile titanium dioxide and water according to the conventional coating preparation process, and the intumescent fire retardant coating is prepared under the condition that the processing temperature does not exceed 150°C.
[0055] It should be noted that the preferred addition amount of the stabilized chlorinated alkanes in the intumescent fire-retardant coating formulation system is 20% (mass percentage). When the addition amount is less than 15%, the stabilized chlorinated alkanes do not sufficiently assist in the foaming of the intumescent charred layer of the coating, resulting in a decrease in flame-retardant effect. When the addition amount exceeds 25%, the uniformity of dispersion of the stabilized chlorinated alkanes in the coating matrix decreases, and local concentration enrichment is likely to occur, leading to preferential degradation in that area during the aging process, resulting in uneven color difference.
[0056] It should be noted that the above-mentioned processing temperature control of no more than 150℃ is based on the characteristic that the thermal decomposition initiation temperature of stabilized chlorinated alkanes treated with high-efficiency composite stabilizers is ≥180℃. A safety margin of ≥30℃ is maintained between the upper limit of processing temperature of 150℃ and the thermal decomposition initiation temperature of 180℃ to ensure that stabilized chlorinated alkanes will not trigger thermal degradation due to local overheating under mechanical shear heating conditions such as stirring, grinding and dispersion in coating preparation.
[0057] It should be noted that the mass ratio of each component in the above-mentioned intumescent fire-retardant coating formulation system is as follows: ammonium polyphosphate 18-25 parts, pentaerythritol 8-15 parts, melamine 8-15 parts, stabilized chlorinated alkanes 15-25 parts, rutile titanium dioxide (particle size 0.2-0.4 μm) 3-7 parts, water 15-22 parts, and the remainder is coating film-forming resin and additives. In this formulation, ammonium polyphosphate serves as the acid source, pentaerythritol as the carbon source, and melamine as the gas source; these three components constitute the basic framework of the intumescent flame-retardant system. The stabilized chlorinated alkanes in this intumescent flame-retardant system also have the functions of assisting in flame retardancy and plasticizing foaming.
[0058] Furthermore, the preferred mass ratio of each component in the above-mentioned intumescent fire-retardant coating formulation system is as follows: 21 parts ammonium polyphosphate, 11.5 parts pentaerythritol, 11.5 parts melamine, 20 parts stabilized chlorinated alkanes, 4.7 parts rutile titanium dioxide, 18.2 parts water, and the remainder being coating film-forming resin and additives.
[0059] Furthermore, the final product of the intumescent fire-retardant coating obtained in step 4 was characterized in the following manner: a standard sample (dry film thickness 500±25 μm) was prepared using the coating film, and a colorimeter was used according to CIE standards. The initial chromaticity value was determined in the color space, where Brightness index The coordinates are red and green. The coordinates are for yellow and blue hues. The standard sample is placed in a xenon lamp aging chamber and subjected to accelerated aging testing according to GB / T 16422.2 standard. After aging for 500 hours, the colorimetric value is measured again, and the color difference is calculated. ,in , , These represent the differences in chromaticity coordinates before and after aging, and the color difference of a qualified product. It should not exceed 3.0; at the same time, infrared spectroscopy analysis was performed on the intumescent fire-retardant coating products to confirm the chemical integrity of each active group (epoxy group, mercapto group, phosphite group) of the high-efficiency composite stabilizer in the coating system.
[0060] Technical effects of the present invention This invention utilizes ethylene glycol glycidyl ether and the epoxy groups in epoxidized soybean oil as hydrogen chloride scavengers, methyl tin thiolate as a heat stabilizer for unstable carbon-chlorine bonds, and triphenyl phosphite as a regeneration synergist for the methyl tin thiolate heat stabilizer, supplemented by 2-hydroxy-4-n-octyloxybenzophenone to inhibit UV-induced degradation at its source and tetra[ [3,5-Di-tert-butyl-4-hydroxyphenyl)propionic acid] pentaerythritol ester terminates free radical chain reactions, forming a highly efficient composite stabilizer system in a chlorinated alkane matrix that encompasses triple protection functions of light stability, thermal stability, and oxidative stability. A clear synergistic relationship exists among the components of this highly efficient composite stabilizer system: ethylene glycol glycidyl ether and epoxidized soybean oil capture hydrogen chloride, reducing the acidity of the system and providing a low-acid environment for the methyltin thiolate heat stabilizer to maintain its active coordination structure; triphenyl phosphite reduces and regenerates inactivated tin chloride, extending the effective stabilization period of the methyltin thiolate heat stabilizer; 2-hydroxy-4-n-octyloxybenzophenone reduces the probability of homolytic cleavage of carbon-chlorine bonds from the photoinitiation stage, reducing the total amount of degradation products requiring treatment with methyltin thiolate heat stabilizers and epoxides; tetra[ [3,5-Di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester terminates the initiated free radical chain reaction, serving as the last line of defense in the entire high-efficiency composite stabilizer system. The synergistic effect of the above components enables the high-efficiency composite stabilizer system to continuously inhibit the dechlorination degradation of chlorinated alkanes under the combined effects of light, heat, and oxygen in service environments, thereby inhibiting yellowing of the coating and increased color difference.
[0061] Meanwhile, this invention employs a gradient-temperature chlorination process during the preparation of chlorinated alkanes, resulting in a more uniform distribution of chlorine atoms in the alkane molecular chain and reducing the proportion of unstable chlorine atoms (tertiary carbon-position chlorine and allyl-position chlorine) in the molecular structure. This improves the inherent thermal stability of the chlorinated alkane base material from the perspective of raw material quality. The chlorinated alkane base material obtained through the gradient-temperature chlorination process has a thermal decomposition onset temperature of no less than 180°C, which is higher than that of the product obtained through a one-step isothermal chlorination process. This provides a wider temperature window for thermal safety during subsequent coating processing and service.
[0062] Furthermore, by controlling the addition amount of stabilized chlorinated alkanes in the intumescent fire-retardant coating formulation system within the range of 15% to 25% and limiting the processing temperature to below 150°C, the stabilized chlorinated alkanes can exert a full flame-retardant and plasticizing effect in the coating matrix without causing local degradation and discoloration due to uneven dispersion caused by excessive addition, thus achieving a balance between flame-retardant performance and color stability.
[0063] Furthermore, the epoxidized soybean oil used in this invention is derived from renewable vegetable oils, and has a lower carbon footprint compared to petroleum-based epoxy plasticizers; the sodium carbonate aqueous solution neutralization and deacidification process replaces the traditional strong alkali washing process, reducing the treatment load of wastewater pH adjustment; the gradient temperature chlorination process reduces the generation of polychlorinated byproducts by improving the uniformity of chlorine atom distribution, thereby improving raw material utilization. These features make the process of this invention demonstrate environmental advantages in terms of raw material source, waste generation, and post-treatment load.
[0064] Example 1 Step 1, Preparation of High-Efficiency Composite Stabilizer: Premix 3 parts of epoxidized soybean oil and 2 parts of ethylene glycol glycidyl ether at 60℃ until homogeneous, then add 1 part of triphenyl phosphite and tetramethyl phthalate sequentially. 0.5 parts of pentaerythritol ester (-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) and 0.5 parts of 2-hydroxy-4-n-octyloxybenzophenone were dissolved. Finally, 1 part of methyltin thiolsate heat stabilizer was added. The mixture was stirred and mixed at 60°C and 200 rpm for 20 minutes to obtain a uniform and transparent high-efficiency composite stabilizer. Visual inspection showed no layering or precipitation, and the product was deemed qualified.
[0065] Step 2, Gradient-temperature chlorination of chlorinated alkanes: Straight-chain alkane feedstock (C14-C17) and 0.1% sodium dodecyl sulfate dispersant (by mass of the feedstock) are added to a chlorination reactor. The mixture is stirred at 300 rpm at room temperature until homogeneous. Dry chlorine gas with a purity of not less than 99.5% is introduced, and chlorination is carried out according to the following gradient-temperature procedure: In the first stage, chlorine gas is introduced at 60°C and reacted for 1 hour; the temperature is increased to 75°C at a rate of 1°C / min, and chlorine gas is introduced again in the second stage for 1.5 hours; then the temperature is increased to 85°C at a rate of 1°C / min, and chlorine gas is introduced again in the third stage for 1.5 hours, for a total reaction time of 4 hours. After the third stage, dry nitrogen gas (purity not less than 99.9%, purging flow rate 3 times the effective volume of the reactor / hour) is introduced at 85°C for 15 minutes to remove residual chlorine and hydrogen chloride. Subsequently, the system was neutralized and deacidified with a 5% sodium carbonate aqueous solution, with the amount of sodium carbonate added being 1.05 times the theoretical neutralization equivalent. The pH of the system was adjusted to 7.0, and then washed with deionized water until the pH of the washing solution was 6.5. The system was then dried at 80°C for 2 hours. The chlorine content was confirmed to be 68% by gas chromatography, and the thermal decomposition initiation temperature was determined by thermogravimetric analysis (nitrogen atmosphere, heating rate 10°C / min).
[0066] Step 3, compounding of the high-efficiency composite stabilizer with chlorinated alkanes: The chlorinated alkane base material obtained in Step 2 and the high-efficiency composite stabilizer obtained in Step 1 are weighed at a mass ratio of 100:0.5, added to a stirred tank under nitrogen protection, and stirred and mixed at 60℃ and 200 rpm for 30 minutes to obtain stabilized chlorinated alkanes. The absorbance at 400 nm was measured by UV-Vis spectrophotometry and compared with that of unstabilized chlorinated alkanes to confirm that the absorbance increase did not exceed 0.05.
[0067] Step 4, Adding stabilized chlorinated alkanes to the fire-retardant coating formulation: Add 15% (mass percentage) of stabilized chlorinated alkanes to an intumescent fire-retardant coating formulation system containing 18 parts ammonium polyphosphate, 8 parts pentaerythritol, 8 parts melamine, 3 parts rutile titanium dioxide (0.2 μm particle size), 15 parts water, and the remaining film-forming resin and additives. The intumescent fire-retardant coating is prepared by stirring, dispersing, and grinding under a processing temperature not exceeding 150℃. Using a standard sample with a dry film thickness of 500±25 μm, according to CIE... The initial chromaticity value was measured in a color space. After aging in a xenon lamp aging chamber for 500 hours according to GB / T 16422.2 standard, the chromaticity value was measured again, and the color difference was calculated. ,in , , These represent the differences in brightness index, red-green hue coordinates, and yellow-blue hue coordinates before and after aging.
[0068] Example 2 Step 1, Preparation of High-Efficiency Composite Stabilizer: 8 parts of epoxidized soybean oil and 5 parts of ethylene glycol glycidyl ether are premixed evenly at 60℃, then 3 parts of triphenyl phosphite and tetramethyl methacrylate are added sequentially. 1.5 parts of pentaerythritol ester (-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) and 2 parts of 2-hydroxy-4-n-octyloxybenzophenone were added after the above components were fully dissolved. Finally, 3 parts of methyltin thiolsate heat stabilizer were added and stirred at 80°C and 400 rpm for 40 minutes to obtain a uniform and transparent high-efficiency composite stabilizer.
[0069] Step 2, Gradient-temperature chlorination of chlorinated alkanes: Straight-chain alkane feedstock (C14-C17) and 0.5% sodium dodecyl sulfate dispersant (by mass of the feedstock) are added to a chlorination reactor. The mixture is stirred at 500 rpm at room temperature until homogeneous. Dry chlorine gas with a purity of not less than 99.5% is introduced, and chlorination is carried out according to the following gradient-temperature procedure: In the first stage, chlorine gas is introduced at 70°C and reacted for 2 hours; in the second stage, the temperature is increased to 85°C at a rate of 3°C / min, and chlorine gas is introduced again for 3 hours; then, the temperature is increased to 95°C at a rate of 3°C / min, and chlorine gas is introduced again for 3 hours, for a total reaction time of 8 hours. After the third stage, the reactor is purged at 90°C with dry nitrogen gas at a flow rate 5 times the effective volume of the reactor per hour for 30 minutes to remove residual chlorine and hydrogen chloride. Subsequently, the system was neutralized and deacidified with a 10% sodium carbonate aqueous solution, with the amount of sodium carbonate added being 1.10 times the theoretical neutralization equivalent. The pH of the system was adjusted to 8.0, and then washed with deionized water until the pH of the washing solution was 7.5. The system was then dried at 100°C for 4 hours. The chlorine content was confirmed to be 72% by gas chromatography, and the thermal decomposition initiation temperature was determined by thermogravimetric analysis.
[0070] Step 3, compounding of high-efficiency composite stabilizer and chlorinated alkanes: Weigh the chlorinated alkane base material obtained in step 2 and the high-efficiency composite stabilizer obtained in step 1 at a mass ratio of 100:2, and stir and mix them for 60 minutes at 80℃ and 400 rpm under nitrogen protection to obtain stabilized chlorinated alkanes. Take a sample and measure the increase in absorbance at 400 nm.
[0071] Step 4, Adding stabilized chlorinated alkanes to the fire-retardant coating formulation: Add 25% (mass percentage) of stabilized chlorinated alkanes to a formulation system containing 25 parts ammonium polyphosphate, 15 parts pentaerythritol, 15 parts melamine, 7 parts rutile titanium dioxide (0.4 μm particle size), 22 parts water, and the remaining film-forming resin and additives. Prepare an intumescent fire-retardant coating at a processing temperature not exceeding 150℃. Measure the initial color value and the color after 500 hours of aging. .
[0072] Example 3 Step 1, Preparation of High-Efficiency Composite Stabilizer: 5 parts of epoxidized soybean oil and 3 parts of ethylene glycol glycidyl ether are premixed evenly at 60℃, then 2 parts of triphenyl phosphite and tetramethyl phthalate are added sequentially. One part of pentaerythritol ester (3,5-di-tert-butyl-4-hydroxyphenyl)propionate and one part of 2-hydroxy-4-n-octyloxybenzophenone were added. After the above components were fully dissolved, two parts of methyltin thiolsate heat stabilizer were added. The mixture was stirred and mixed at 70°C and 300 rpm for 30 minutes to obtain a uniform and transparent high-efficiency composite stabilizer.
[0073] Step 2, Gradient-temperature chlorination of chlorinated alkanes: Straight-chain alkane feedstock (C14-C17) and 0.3% sodium dodecyl sulfate dispersant (by mass of the feedstock) are added to a chlorination reactor. The mixture is stirred at 400 rpm at room temperature until homogeneous. Dry chlorine gas with a purity of not less than 99.5% is introduced, and chlorination is carried out according to the following gradient-temperature procedure: In the first stage, chlorine gas is introduced at 65°C and the reaction proceeds for 1.5 hours; the temperature is increased to 80°C at a rate of 2°C / min, and chlorine gas is introduced again for 2.25 hours in the second stage; then the temperature is increased to 90°C at a rate of 2°C / min, and chlorine gas is introduced again for 2.25 hours in the third stage, for a total reaction time of 6 hours. After the third stage, the reactor is purged at 87.5°C with dry nitrogen gas at a flow rate of 4 times the effective volume of the reactor per hour for 22.5 minutes to remove residual chlorine and hydrogen chloride. Subsequently, the system was neutralized and deacidified with a 7.5% sodium carbonate aqueous solution, with the amount of sodium carbonate added being 1.075 times the theoretical neutralization equivalent. The pH of the system was adjusted to 7.5, and then washed with deionized water until the pH of the washing solution was 7.0. The system was then dried at 90°C for 3 hours. The chlorine content was confirmed to be 70% by gas chromatography, and the thermal decomposition initiation temperature was determined by thermogravimetric analysis.
[0074] Step 3, compounding of high-efficiency composite stabilizer and chlorinated alkanes: Weigh the chlorinated alkane base material obtained in Step 2 and the high-efficiency composite stabilizer obtained in Step 1 at a mass ratio of 100:1.5, stir and mix them for 60 minutes at 75℃ and 300 rpm under nitrogen protection to obtain stabilized chlorinated alkanes, and take samples to measure the increase in absorbance at 400 nm.
[0075] Step 4, Addition of stabilized chlorinated alkanes to the fire-retardant coating formulation: Add 20% (mass percentage) of stabilized chlorinated alkanes to a formulation system containing 21 parts ammonium polyphosphate, 11.5 parts pentaerythritol, 11.5 parts melamine, 4.7 parts rutile titanium dioxide (0.3 μm particle size), 18.2 parts water, and the remaining film-forming resin and additives. Prepare an intumescent fire-retardant coating at a processing temperature not exceeding 150℃. Measure the initial color value and the color after 500 hours of aging. .
[0076] Example 4 Step 1, Preparation of high-efficiency composite stabilizer: 4 parts of epoxidized soybean oil and 2.5 parts of ethylene glycol glycidyl ether were premixed evenly at 60℃, and then 1.5 parts of triphenyl phosphite and tetramethyl phthalate were added sequentially. 0.8 parts of pentaerythritol ester (-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) and 0.8 parts of 2-hydroxy-4-n-octyloxybenzophenone were dissolved. Finally, 1.5 parts of methyltin thiolsate heat stabilizer were added. The mixture was stirred and mixed at 65°C and 250 rpm for 25 minutes to obtain a uniform and transparent high-efficiency composite stabilizer.
[0077] Step 2, Gradient-temperature chlorination of chlorinated alkanes: Straight-chain alkane feedstock (C14-C17) and 0.2% sodium dodecyl sulfate dispersant (by mass of the feedstock) are added to a chlorination reactor. The mixture is stirred at 350 rpm at room temperature until homogeneous. Dry chlorine gas with a purity of not less than 99.5% is introduced, and chlorination is carried out according to the following gradient-temperature procedure: In the first stage, chlorine gas is introduced at 62°C and the reaction proceeds for 1.2 hours; the temperature is then increased to 78°C at a rate of 1.5°C / min, and chlorine gas is introduced again for 2 hours in the second stage; the temperature is then increased to 88°C at a rate of 1.5°C / min, and chlorine gas is introduced again for 2 hours in the third stage, for a total reaction time of 5 hours. After the third stage, the reactor is purged at 86°C with dry nitrogen gas at a flow rate 3.5 times the effective volume of the reactor per hour for 20 minutes to remove residual chlorine and hydrogen chloride. Subsequently, the system was neutralized and deacidified with a 6% sodium carbonate aqueous solution, with the amount of sodium carbonate added being 1.06 times the theoretical neutralization equivalent. The pH of the system was adjusted to 7.2, and then washed with deionized water until the pH of the washing solution was 6.8. The system was then dried at 85°C for 2.5 hours. The chlorine content was confirmed to be 69% by gas chromatography, and the thermal decomposition initiation temperature was determined by thermogravimetric analysis.
[0078] Step 3, compounding of high-efficiency composite stabilizer and chlorinated alkanes: Weigh the chlorinated alkane base material obtained in Step 2 and the high-efficiency composite stabilizer obtained in Step 1 at a mass ratio of 100:1, stir and mix them for 40 minutes at 65℃ and 250 rpm under nitrogen protection to obtain stabilized chlorinated alkanes, and take samples to measure the increase in absorbance at 400 nm.
[0079] Step 4, Adding stabilized chlorinated alkanes to the fire-retardant coating formulation: Add 17% (mass percentage) of stabilized chlorinated alkanes to a formulation system containing 19 parts ammonium polyphosphate, 9 parts pentaerythritol, 9 parts melamine, 4 parts rutile titanium dioxide (0.25 μm particle size), 16 parts water, and the remaining film-forming resin and additives. Prepare an intumescent fire-retardant coating at a processing temperature not exceeding 150℃. Measure the initial color value and the color after 500 hours of aging. .
[0080] Example 5 Step 1, Preparation of the high-efficiency composite stabilizer: 6.5 parts of epoxidized soybean oil and 4 parts of ethylene glycol glycidyl ether were premixed evenly at 60℃, and then 2.5 parts of triphenyl phosphite and tetramethyl phthalate were added sequentially. 1.2 parts of pentaerythritol ester (-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) and 1.5 parts of 2-hydroxy-4-n-octyloxybenzophenone were added. After the above components were fully dissolved, 2.5 parts of methyltin thiolsate heat stabilizer were added. The mixture was stirred and mixed at 75°C and 350 rpm for 35 minutes to obtain a uniform and transparent high-efficiency composite stabilizer.
[0081] Step 2, Gradient-temperature chlorination of chlorinated alkanes: Straight-chain alkane feedstock (C14-C17) and 0.4% sodium dodecyl sulfate dispersant (by mass of the feedstock) are added to a chlorination reactor. The mixture is stirred at 450 rpm at room temperature until homogeneous. Dry chlorine gas with a purity of not less than 99.5% is introduced, and chlorination is carried out according to the following gradient-temperature procedure: In the first stage, chlorine gas is introduced at 68°C and the reaction proceeds for 1.8 hours; the temperature is then increased to 83°C at a rate of 2.5°C / min, and chlorine gas is introduced again for 2.5 hours in the second stage; the temperature is then increased to 93°C at a rate of 2.5°C / min, and chlorine gas is introduced again for 2.5 hours in the third stage, for a total reaction time of 7 hours. After the third stage, the reactor is purged at 89°C with dry nitrogen gas at a flow rate 4.5 times the effective volume of the reactor per hour for 25 minutes to remove residual chlorine and hydrogen chloride. Subsequently, the system was neutralized and deacidified with a 9% sodium carbonate aqueous solution, with the amount of sodium carbonate added being 1.09 times the theoretical neutralization equivalent. The pH of the system was adjusted to 7.8, and then washed with deionized water until the pH of the washing solution was 7.3. The system was then dried at 95°C for 3.5 hours. The chlorine content was confirmed to be 71% by gas chromatography, and the thermal decomposition initiation temperature was determined by thermogravimetric analysis.
[0082] Step 3, compounding of high-efficiency composite stabilizer and chlorinated alkanes: Weigh the chlorinated alkane base material obtained in Step 2 and the high-efficiency composite stabilizer obtained in Step 1 at a mass ratio of 100:1.8, stir and mix them for 55 minutes at 78℃ and 350 rpm under nitrogen protection to obtain stabilized chlorinated alkanes, and take samples to measure the increase in absorbance at 400 nm.
[0083] Step 4, Addition of stabilized chlorinated alkanes to the fire-retardant coating formulation: Add 23% (mass percentage) of stabilized chlorinated alkanes to a formulation system containing 23 parts ammonium polyphosphate, 13 parts pentaerythritol, 13 parts melamine, 6 parts rutile titanium dioxide (0.35 μm particle size), 20 parts water, and the remaining film-forming resin and additives. Prepare an intumescent fire-retardant coating at a processing temperature not exceeding 150℃. Measure the initial color value and the color after 500 hours of aging. .
[0084] Example 6 Steps 1, 3, and 4 are exactly the same as in Example 3: The high-efficiency composite stabilizer formulation in step 1 consists of 5 parts epoxidized soybean oil, 3 parts ethylene glycol glycidyl ether, 2 parts triphenyl phosphite, and tetra[ One part of pentaerythritol ester (3,5-di-tert-butyl-4-hydroxyphenyl)propionate, one part of 2-hydroxy-4-n-octyloxybenzophenone, and two parts of methyltin thiolsate heat stabilizer were stirred and mixed at 70°C and 300 rpm for 30 minutes. In step 3, the mass ratio of chlorinated alkane base material to high-efficiency composite stabilizer was 100:1.5, and the mixture was stirred and mixed at 75°C and 300 rpm for 60 minutes. In step 4, the amount of stabilized chlorinated alkane added was 20%, and the amount of each component in the formulation was the same as in Example 3.
[0085] Step 2 (One-step isothermal chlorination, the only difference from Example 3): Straight-chain alkane feedstock (C14-C17) and 0.3% sodium dodecyl sulfate dispersant (by mass of the feedstock) were added to a chlorination reactor. The mixture was stirred at 400 rpm at room temperature until homogeneous. Dry chlorine gas with a purity of not less than 99.5% was introduced, and the one-step chlorination reaction was carried out at a constant temperature of 85°C for 6 hours without a gradient temperature increase program. After the reaction, the post-treatment steps (nitrogen purging, neutralization and deacidification with sodium carbonate aqueous solution, washing with deionized water, and drying by forced air) were the same as in Example 3. Gas chromatography confirmed a chlorine content of 70%, and thermogravimetric analysis determined the thermal decomposition initiation temperature. The results were compared with those of Example 3.
[0086] Comparative Example 1 Steps 2, 3, and 4 are exactly the same as in Example 3.
[0087] Step 1 (omitting 2-hydroxy-4-n-octyloxybenzophenone, other components are the same as in Example 3): Premix 5 parts of epoxidized soybean oil and 3 parts of ethylene glycol glycidyl ether at 60°C until homogeneous, then add 2 parts of triphenyl phosphite and tetramethyl phthalate sequentially. One part of pentaerythritol 3,5-di-tert-butyl-4-hydroxyphenyl)propionate was added, and after the above components were fully dissolved, two parts of methyltin thiolate heat stabilizer were added. 2-hydroxy-4-n-octyloxybenzophenone was not added. The mixture was stirred and mixed at 70°C and 300 rpm for 30 minutes to obtain a composite stabilizer without UV-absorbing components. The remaining steps were the same as in Example 3, and finally, an intumescent fire-retardant coating without UV absorbers was obtained. The initial color value and the color value after 500 hours of aging were measured. and .
[0088] Comparative Example 2 Steps 1, 3, and 4 are exactly the same as in Example 3.
[0089] Step 2 (One-step isothermal chlorination, the only difference from Example 3): Completely identical to Step 2 of Example 6, i.e., one-step chlorination reaction at a constant temperature of 85°C for 6 hours, without a gradient temperature increase program. Post-processing steps are the same as in Example 3. Gas chromatography confirms a chlorine content of 70%, thermogravimetric analysis determines the thermal decomposition initiation temperature, and comparison is made with Example 3. Finally, a fire-retardant coating is obtained, and the initial color value and the color after 500 hours of aging are measured. .
[0090] Comparative Example 3 Steps 2 and 4 are exactly the same as in Example 3.
[0091] Step 1 (replacing all high-efficiency composite stabilizers with a single methyltin thiolate heat stabilizer): Weigh out 2 parts of the methyltin thiolate heat stabilizer separately, without adding ethylene glycol glycidyl ether, triphenyl phosphite, epoxidized soybean oil, 2-hydroxy-4-n-octyloxybenzophenone, and tetra[ [3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester was stirred and kept at 70°C and 300 rpm for 30 minutes to obtain a liquid monomethyltin thiolate stabilizer.
[0092] Step 3 (Compounding): The chlorinated alkane base obtained in Step 2 and the above-mentioned single methyltin thiolate stabilizer liquid were weighed at a mass ratio of 100:1.5. The mixture was stirred and mixed for 60 minutes at 75°C and 300 rpm under nitrogen protection to obtain chlorinated alkane stabilized only by a single methyltin thiolate. Step 4 is the same as in Example 3, finally yielding a fire-retardant coating. The initial color value and the color after 500 hours of aging were measured. and .
[0093] Experimental Objective Using the intumescent fire-retardant coating samples prepared in Examples 1 to 6 and Comparative Examples 1 to 3 as test objects, the core technical effects of the present invention were verified through the following four sets of comparative experiments: First, based on Examples 1 to 5, it was verified that under the condition of full coverage of parameter range, each example could meet the color difference requirement after aging for 500 hours. The following are the key points: First, the qualified indicators; second, the necessity of 2-hydroxy-4-n-octyloxybenzophenone to inhibit photo-induced degradation was verified by comparing Example 3 with Comparative Example 1; third, the contribution of gradient temperature chlorination program to the thermal decomposition initiation temperature of chlorinated alkane base material and the color stability of coating was verified by comparing Example 3 with Comparative Example 2 and Example 6 with Comparative Example 2; fourth, the superiority of the multi-component synergistic system of high-efficiency composite stabilizer over single methyltin thiolate stabilizer in continuously inhibiting yellowing under long-term aging conditions was verified by comparing Example 3 with Comparative Example 3.
[0094] Experimental sample preparation Stabilized chlorinated alkanes and intumescent fire-retardant coatings were prepared according to the processes described in Examples 1 to 6 and Comparative Examples 1 to 3, resulting in a total of 9 samples, numbered sequentially as Sample 1 (Example 1) to Sample 6 (Example 6), Sample 7 (Comparative Example 1), Sample 8 (Comparative Example 2), and Sample 9 (Comparative Example 3). After preparation, the coatings were applied to surface-treated Q235 carbon steel plates (150 mm × 70 mm × 1 mm) using a wire bar coater and dried and cured for 7 days under standard conditions (temperature 23±2℃, relative humidity 50±5%). The dry film thickness was confirmed to be 500±25 μm using a micrometer, serving as the standard sample for subsequent color difference measurement and aging tests.
[0095] Experimental conditions The conditions for determining the thermal decomposition initiation temperature of the chlorinated alkane base material in step 2 are as follows: thermogravimetric analyzer, nitrogen atmosphere (flow rate 50 mL / min), heating rate 10℃ / min, temperature range 50~500℃, and the temperature corresponding to the sample mass loss reaching 5% of the initial mass is taken as the thermal decomposition initiation temperature.
[0096] The conditions for determining the dispersion uniformity of stabilized chlorinated alkanes in step 3 are as follows: UV-Vis spectrophotometer, wavelength 400 nm, with unstabilized chlorinated alkanes as a reference, to measure the absorbance increment.
[0097] Coating color difference measurement conditions: colorimeter, CIE Color space, measuring aperture 8 mm, standard light source D65, measuring angle 10°, 5 points were measured for each sample and the average value was taken.
[0098] Accelerated aging test conditions: Xenon lamp aging chamber, performed according to GB / T 16422.2 standard, irradiance 0.51 W / (340 nm), black mark temperature 65±3℃, relative humidity 50±5%, continuous light exposure, aging time 500 hours.
[0099] Experimental steps The chlorine content of the chlorinated alkane base material (product of step 2) in each group of samples was determined by gas chromatography, and the thermal decomposition initiation temperature was determined by thermogravimetric analysis. The data were recorded. Stabilized chlorinated alkanes (products from step 3) were sampled from each group of samples, and the absorbance increment at 400 nm was measured using a UV-Vis spectrophotometer to confirm the uniformity of dispersion. The initial colorimeter values of each group of standard samples were measured before aging. , , value; Each set of standard samples was placed in a xenon lamp aging chamber and aged continuously for 500 hours according to GB / T 16422.2 standard; After aging, the sample was removed, equilibrated under standard conditions for 2 hours, and then measured again using a colorimeter. , , Value, calculation , , and color difference ,in Brightness index The coordinates are red and green. The coordinates are yellow and blue. Total color difference; The results of each group were summarized and statistically analyzed, and the performance change ratio of each comparative example was calculated based on Example 3.
[0100] Experimental or test results Table 1. Preparation parameters and characterization results of chlorinated alkane-based materials for each group of samples. ; As shown in Table 1, the thermal decomposition initiation temperature of the chlorinated alkane base materials obtained by the gradient temperature chlorination process (samples 1 to 5, 7, and 9) is not lower than 180℃, meeting the qualified product indicators. However, samples 6 and 8, which were chlorinated at a constant temperature of 85℃ using a one-step method, had the same measured chlorine content of 70.0%, but their thermal decomposition initiation temperature was only 171℃, a decrease of 17℃ compared to sample 3 (188℃) obtained by the gradient temperature process, representing a decrease of approximately 9.0%. This indicates that the gradient temperature process reduces the proportion of unstable chlorine atoms (chlorine at the tertiary carbon site and chlorine at the allyl site) in the molecular structure, giving the chlorinated alkane base materials higher inherent thermal stability at the same chlorine content.
[0101] Table 2 Composition of each group of high-efficiency composite stabilizer formulations ; Table 3 Formulation parameters and mixing mass ratio of each group of intumescent fire-retardant coatings in step 3 ; Table 4. Colorimetric data and color difference results of each group of intumescent fire-retardant coatings before and after 500 hours of aging. ; As shown in Table 4, the color difference of Examples 1 to 5 (Sample 1 to Sample 5) that meet the complete process conditions of this invention after 500 hours of xenon lamp aging is... All values did not exceed 2.10, far below the acceptable limit of 3.0, demonstrating excellent color stability. Sample 3 (Example 3) with the preferred formulation... A comparative analysis was conducted using as a benchmark: Comparison of Example 3 and Comparative Example 1: Sample 7 (Comparative Example 1, omitting 2-hydroxy-4-n-octyloxybenzophenone) Compared to sample 3 ( Increased by 228%, The yellowing intensified significantly from +1.4 to +4.8, failing to meet the acceptable standards. This indicates that the selective absorption and dissipation of 2-hydroxy-4-n-octyloxybenzophenone by ultraviolet radiation in the 280–380 nm band is essential for suppressing photo-induced homolytic cleavage of carbon-chlorine bonds. Omitting this component leaves the system without protection during the photoinitiation process, leading to a significant increase in the degradation rate of chlorinated alkanes, ultimately resulting in a marked deterioration in the color stability of the coating.
[0102] Comparison of Example 3 and Comparative Example 2: Sample 8 (Comparative Example 2, one-step isothermal chlorination combined with a high-efficiency composite stabilizer) The concentration of chlorine atoms increased by 179% compared to sample 3, also failing to meet the qualification requirements. Combined with the fact that the thermal decomposition initiation temperature of sample 8 in Table 1 was only 171℃ (17℃ lower than sample 3), this indicates that the one-step isothermal chlorination method resulted in a higher proportion of unstable chlorine atoms in the chlorinated alkane base material, making it more prone to dechlorination degradation during aging. Even though the highly efficient composite stabilizer system has the function of capturing and terminating degradation intermediates, it is difficult to completely compensate for the accelerated degradation caused by the structural defects of the base material. Example 6 (sample 6) used the same one-step isothermal chlorination method but combined with a highly efficient composite stabilizer. It is in a qualified critical state, similar to Example 3 ( The color difference increased by 87% compared to the previous year, further confirming the importance of the gradient heating process in improving the inherent thermal stability of chlorinated alkane base materials.
[0103] Comparison of Example 3 and Comparative Example 3: Sample 9 (Comparative Example 3, monomethyltin thiolate stabilizer) It increased by 272% compared to sample 3. The yellowing level was as high as +5.5, the highest among all samples, and it did not meet the qualification criteria. During long-term aging, the single methyltin thiolate stabilizer lacked the synergistic effect of hydrogen chloride capture by ethylene glycol glycidyl ether and epoxidized soybean oil, the regeneration synergistic effect of triphenyl phosphite, and the dual protection of light and oxidation stability. Its effective stabilizing capacity rapidly decreased with prolonged aging time, and it could not continuously inhibit the dechlorination degradation of chlorinated alkanes. This fully demonstrates that the multi-component synergistic system of the high-efficiency composite stabilizer has significant technical advantages over a single stabilizer.
[0104] Based on the above experimental results, the stabilization process of the weather-resistant and anti-yellowing chlorinated alkane intumescent fire-retardant coating described in this invention, through the combined effect of the multi-component synergistic protection of a high-efficiency composite stabilizer and a gradient temperature chlorination procedure, reduces the color difference of the intumescent fire-retardant coating after 500 hours of accelerated aging under a xenon lamp. (Examples 1 to 5) Stable color retention was achieved within a wide process window covering the endpoint values to the preferred values of the parameter range. Compared with the control schemes that omit the UV absorber, use one-step constant temperature chlorination, or use a single stabilizer, the color stability was improved by 179% to 272%, effectively solving the yellowing problem of chlorinated alkanes in fire-retardant coatings during long-term outdoor service.
[0105] The embodiments of the present invention have been described above. However, the embodiments are not limited to the specific implementation methods described above. The specific implementation methods described above are merely illustrative and not restrictive. Those skilled in the art can make more equivalent embodiments under the guidance of the present embodiments, and all of them are within the protection scope of the present embodiments.
Claims
1. A stabilization process for a weather-resistant, anti-yellowing chlorinated alkane intumescent fire-retardant coating, characterized in that, Includes the following steps: Step 1: Ethylene glycol glycidyl ether, methyl tin thiolsate heat stabilizer, triphenyl phosphite, epoxidized soybean oil, 2-hydroxy-4-n-octyloxybenzophenone, and pentaerythritol tetrapropionate are stirred and mixed at 60-80°C for 20-40 minutes to obtain a high-efficiency composite stabilizer; the mass parts of each component are: 2-5 parts of ethylene glycol glycidyl ether, 1-3 parts of methyl tin thiolsate heat stabilizer, 1-3 parts of triphenyl phosphite, 3-8 parts of epoxidized soybean oil, 0.5-2 parts of 2-hydroxy-4-n-octyloxybenzophenone, and 0.5-1.5 parts of pentaerythritol tetrapropionate; Step 2: Add the straight-chain alkane raw material and dispersant to the chlorination reactor, introduce dry chlorine gas and carry out the chlorination reaction according to the gradient temperature program. After deacidification, water washing and drying, chlorinated alkane base material with chlorine content of 68% to 72% is obtained. Step 3: Mix the chlorinated alkane base material and the high-efficiency composite stabilizer at a mass ratio of 100:0.5-2 at 60-80°C for 30-60 minutes to obtain stabilized chlorinated alkane. Step four: Add stabilized chlorinated alkanes at a mass percentage of 15% to 25% to the intumescent fire retardant coating formulation system, and prepare the intumescent fire retardant coating at a processing temperature not exceeding 150°C.
2. The stabilization process for a weather-resistant, anti-yellowing chlorinated alkane intumescent fire-retardant coating according to claim 1, characterized in that, The mass fractions of each component in step one are as follows: 3 parts ethylene glycol glycidyl ether, 2 parts methyl tin thiolsate heat stabilizer, 2 parts triphenyl phosphite, 5 parts epoxidized soybean oil, 1 part 2-hydroxy-4-n-octyloxybenzophenone, and 1 part pentaerythritol tetrapropionate.
3. The stabilization process for a weather-resistant, anti-yellowing chlorinated alkane intumescent fire-retardant coating according to claim 1, characterized in that, The order of adding the components in step one is as follows: first, premix the epoxidized soybean oil and ethylene glycol glycidyl ether evenly at 60°C, then add triphenyl phosphite, pentaerythritol tetrapropionate and 2-hydroxy-4-n-octyloxybenzophenone in sequence. After the above components are fully dissolved, add the methyltin thiolsate heat stabilizer. The mixing temperature is controlled at 60-70°C.
4. The stabilization process for a weather-resistant, anti-yellowing chlorinated alkane intumescent fire-retardant coating according to claim 1, characterized in that, The gradient heating process described in step two includes three stages: the first stage involves introducing chlorine gas at 60–70°C for 1–2 hours; the second stage involves raising the reaction temperature to 75–85°C and continuing to introduce chlorine gas for 1.5–3 hours; and the third stage involves raising the reaction temperature to 85–95°C and continuing to introduce chlorine gas for 1.5–3 hours. The total reaction time is controlled within 4–8 hours.
5. The stabilization process for a weather-resistant, anti-yellowing chlorinated alkane intumescent fire-retardant coating according to claim 4, characterized in that, In step two, the heating rate between the first and second stages and between the second and third stages is controlled at 1–3 °C / min; the dispersant is sodium dodecyl sulfate, and the amount added is 0.1%–0.5% of the mass of the straight-chain alkane raw material.
6. The stabilization process according to claim 4, characterized in that, After the third stage reaction in step two is completed, dry nitrogen gas is introduced into the reaction system at 85-90℃ for 15-30 minutes. Then, the system is neutralized and deacidified with a 5%-10% sodium carbonate aqueous solution until the pH of the system is 7.0-8.0, washed with deionized water until the pH of the washing solution is 6.5-7.5, and dried with forced air at 80-100℃ for 2-4 hours.
7. The stabilization process for a weather-resistant, anti-yellowing chlorinated alkane intumescent fire-retardant coating according to claim 1, characterized in that, The chlorinated alkane base material obtained in step two is a straight-chain alkane chloride with a base carbon chain length of C14 to C17, a viscosity of 500 to 3000 mPa·s, and a thermal decomposition initiation temperature of not less than 180℃.
8. The stabilization process for a weather-resistant, anti-yellowing chlorinated alkane intumescent fire-retardant coating according to claim 1, characterized in that, In step three, the mass ratio of chlorinated alkane base material to high-efficiency composite stabilizer is 100:1.5, the stirring temperature is 75℃, the stirring time is 60 minutes, and the compounding operation is carried out under nitrogen protection with a purity of not less than 99.9%.
9. The stabilization process for a weather-resistant, anti-yellowing chlorinated alkane intumescent fire-retardant coating according to claim 1, characterized in that, The mass fractions of each component in the intumescent fire retardant coating formulation system described in step four are as follows: 18-25 parts ammonium polyphosphate, 8-15 parts pentaerythritol, 8-15 parts melamine, 15-25 parts stabilized chlorinated alkanes, 3-7 parts rutile titanium dioxide, 15-22 parts water, and the remainder being coating film-forming resin and additives.
10. An intumescent fire-retardant coating prepared by the stabilization process of a weather-resistant and anti-yellowing chlorinated alkane intumescent fire-retardant coating as described in any one of claims 1 to 9.